Digital Development of Economic Systems in BRICS Countries - Sergey V. Ponomarev; Alexander Yu. Usanov; Ilya E. Pokamestov; Natalia I. Kuzmenko (Вестник Кемеровского государственного университета. Серия: политические, социологические и экономические науки)
As the global political landscape keeps changing, digital development becomes even more important for the BRICS integration. The article describes the benefits of digitalizing the economic systems of the BRICS countries, as well as outlines the opportunities of strengthening their digital potential. The authors analyzed the current dynamics of the digital development in the BRICS countries and assessed the ability of digital technologies to compensate for the negative impact of the COVID-19 pandemic on the BRICS economy. They used a set of standard research methods combined with economic, statistical, and graphic analyses to identify the main integrative directions between the countries that may improve their digital potential. The pandemic widened the gap between Internet use in urban and rural areas but diversified it as e-commerce continued to grow and more and more public services went digital. China and India increased their exports of information and communication goods and services. The article contains some ideas on strengthening the intra-integration cooperation between the BRICS countries in order to expand their digital potential. The indicators of digital development in all BRICS countries increased after the pandemic, and the integration proved effective as a new center of influence in the global economy.